DUKUNGAN KELUARGA PADA LANSIA UNTUK MELAKSANAKAN PROTOKOL KESEHATAN MASA PANDEMIC COVID-19 (Pengabdian kepada Masyakarakat) - Ariani Sulistyorini; Enur Nurhayati Muchsin; Dodik Arso Wibowo (Prosiding SPIKesNas : Seminar Publikasi Ilmiah Kesehatan Nasional, 2022)
Family support is very much needed by the elderly so that their quality of life and health of the elderly can be maintained optimally during the Covid-19 pandemic, and ensure that the elderly are not exposed to Covid-19. Families need to pay attention to health protocols for all family members, especially the elderly, following health protocol rules such as wearing masks, washing hands, and physical distancing. The education or counseling will be held from March 14 to 16, 2022. In RT 11 RW 04 Sumbergedong Village, Trenggalek District, Trenggalek Regency, East Java. the implementation of the activity was assisted by 3 students. The method used was a lecture, discussion/question, and answer. The implementation of activities using leaflet media, providing material using LCD and laptop media. The results of interviews and filling out questionnaires by activity participants about family support for the elderly to implement Health protocols during the covid 19 pandemic, it was found that most respondents had good family support, a small proportion of respondents with sufficient family support were 4 respondents (18%), and some a small number of respondents have less family support as much as 2 respondents (9%). Family support is very necessary for the elderly in implementing health protocols during the covid 19 pandemic. -days during the covid-19 pandemic.